Fabrication of well‐ordered arrays of silicon nanocrystals using a block copolymer mask. Issue 8 (3rd July 2013) - Pellegrino, Paolo; Perego, Michele; Schamm‐Chardon, Sylvie; Seguini, Gabriele; Andreozzi, Andrea; Lupi, Federico Ferrarese; Castro, Celia; Assayag, Gerard Ben
<x xml:space="preserve">Abstract</x> The block copolymer self‐assembly provides a reliable tool for the planar organization of materials at the nanoscale. In this paper, we review our recent achievements in the case of the polystyrene‐b‐poly(methyl‐methacrylate) (PS‐b‐PMMA) polymeric mixture. By the proper choice of deposition and treatment parameters, one can adjust the thickness of the deposited material and transfer the block copolymer cylindrical organization to the material inclusions into the matrix. Silicon nanocrystals (Si‐ncs) have been used as the active material to process, due to its interesting electrical and optical properties for electronic and photonic applications. This material has been fabricated in the form of well‐defined arrays over a macroscopic surface, either by electron beam deposition or by ion beam synthesis. A further, crucial step toward the fabrication of the active area of the device is the formation of Si nanoparticle arrays onto sub‐micrometric trenches defined by graphoepitaxy. The periodicity and the topography of the trenches highly affect the possibility of a conformal deposition of the ordered block polymeric mask, and consequently, of the reproduction of the patterned array of nanocrystals.